2019
DOI: 10.4103/ijpc.ijpc_29_19
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the attitude of healthcare providers, patients, and their families toward “do not resuscitate” orders in an Iranian Oncology Hospital

Abstract: Aim:The decision-making process for do-not-resuscitate (DNR) order has always been challenging. Cultural and religious issues have limited the issuance and execution of DNR orders in Iran. The purpose of this study was to assess the attitude of the nurses, physicians, patients, and their families toward the DNR order.Subjects and Methods:In this cross-sectional study, 343 participants (201 patients, 95 family members, and 47 healthcare providers) from Omid Oncology Hospital, Mashhad, Iran, were surveyed during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In this context, Jure et al (2019) found that gender is one of the elements impacting decisions about autonomy, patient rights, and resuscitation commencement or prevention (Jure et al, 2019). In addition, Fayyazi Bordbar et al (2019) found that gender is a significant factor in deciding on a DNR order, with male caregivers and family members of cancer patients having a more favorable attitude toward the DNR order (Bordbar et al, 2019). In contrast to the current findings, Fallahi et al, 2016 investigated Iranian physicians’ perceptions toward the DNR order and discovered that gender was not a key factor in deciding on a DNR order, and there was no association between gender and attitudes toward a DNR order (Fallahi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, Jure et al (2019) found that gender is one of the elements impacting decisions about autonomy, patient rights, and resuscitation commencement or prevention (Jure et al, 2019). In addition, Fayyazi Bordbar et al (2019) found that gender is a significant factor in deciding on a DNR order, with male caregivers and family members of cancer patients having a more favorable attitude toward the DNR order (Bordbar et al, 2019). In contrast to the current findings, Fallahi et al, 2016 investigated Iranian physicians’ perceptions toward the DNR order and discovered that gender was not a key factor in deciding on a DNR order, and there was no association between gender and attitudes toward a DNR order (Fallahi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of health care providers’ attitudes toward DNR consent, 57% of the respondents indicated that they believed that providing enough information regarding DNR consent to patients was important. However, the execution rate was only 21% [ 14 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, older adult patients with chronic diseases often exhibit poor responses to CPR, which limit their ability to participate in DNR decision-making [ 25 , 26 , 27 , 28 ]. Studies have demonstrated that various factors affect DNR decision-making, including economic status, suggestions from nurses or physicians, education level, place of residence of family members, and sex [ 9 , 14 , 15 ]. A tool for evaluating the extent of the reversibility of a patient’s illness that can be used before the patient is admitted to the hospital [ 29 ] would be helpful in preparing for DNR discussions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations